Pengaruh Pendekatan Berpikir Kausalitik Ber-Scaffolding Dengan Pemberian Tugas Pendahuluan Terhadap Kemampuan Pemecahan Masalah Siswa SMA - Roni Abdani; Joni Rokhmat; Satutik Rahayu (Department of Physics Education, Universitas Mataram, 2018)
This research aims to discover the effect of scaffolding causalitic thinking approach with preliminary task toward impulse and momentum studentÃ¢â¬â¢s problem solving ability (PSA) at X grade. The type of this study is quasi experimental research with post-test only control group design. The research population is all studentÃ¢â¬â¢s of X MIA SMAN 8 Mataram with 33 chosen students from X MIA 1 as experimental class and 32 chosen students from X MIA 3 as control class as the sample by using cluster random sampling. Based on the research finding, it is found that the average score of problem solving ability in experimental class is 65, while the average score of PSA in control class is 53. The PSA data of two classes were normal distributed. According to the result of homogeneity test, it was obtained that both are homogen. The PSA data were analyzed with t-test polled varians. The data analysis showed that tcount was 3,3690 and ttable with significant rate (5%) was 1,9987 which means tcount >ttable.Based on that fact, it can be concluded that there is an effect of scaffolding causalitic-thinking approach with preliminary tasks toward PSA impulse and momentum students at X grade.